1982
DOI: 10.1071/ch9820809
|View full text |Cite
|
Sign up to set email alerts
|

The structure determination of two related eremophilone dimers

Abstract: The first representatives of a new class of eremophilone dimers have been isolated from the wood oil of Eremophila mitchelli and shown by a combination of spectroscopic and X-ray techniques to possess the unusual 1-(8',8'a-dimethylperhydronaphthalen-2'-yl)-1,4,5,10a-tetramethylperhydroanthracene carbon skeleton. These two natural products are the first C30 compounds to be isolated from any member of the genus Eremophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Their isolation and characterisation is complicated because they share similar molecular weights and many were found to co-elute with the major compounds throughout HPLC (both NP and RP) and GC-MS (both polar and apolar systems). Several structural analogues of the eremophilones have been reported in the literature including the aldehyde 2 (Abel and Massy-Westropp, 1985), isoeremophilone (11) (Chetty and Zalkow, 1969), alloeremophilone (12) (Bates and Paknikar., 1966) and the dimers 7 and 8 (Lewis et al, 1979(Lewis et al, , 1982. The analogues, if present, appear to be very minor constituents.…”
Section: Chemical Composition Of the Heartwood Oilmentioning
confidence: 97%
“…Their isolation and characterisation is complicated because they share similar molecular weights and many were found to co-elute with the major compounds throughout HPLC (both NP and RP) and GC-MS (both polar and apolar systems). Several structural analogues of the eremophilones have been reported in the literature including the aldehyde 2 (Abel and Massy-Westropp, 1985), isoeremophilone (11) (Chetty and Zalkow, 1969), alloeremophilone (12) (Bates and Paknikar., 1966) and the dimers 7 and 8 (Lewis et al, 1979(Lewis et al, , 1982. The analogues, if present, appear to be very minor constituents.…”
Section: Chemical Composition Of the Heartwood Oilmentioning
confidence: 97%
“…105 Further research resulted in the isolation of two more dimers, 105-106, possessing the same skeleton as 104. 106 A symmetrical eremophilane dimer 107 was identified as a component of the rhizomes of Farfugium japonica. 107 The dimers virgaurins A-C 108-110, 108-111 111-112 104 and virgaurols A-B 113-114 112 were obtained from the same species, Ligularia virgaurea, collected from a different district in China.…”
Section: Eremophilane Dimersmentioning
confidence: 99%
“…1,5 The natural products isolated from this species include eremophilone [15][16][17] and its derivatives. 4,[18][19][20][21] Oil extracts from this plant have been extensively studied due to their termiticidal and insecticidal activities, [21][22][23][24] and one study has found the wood oil to possess antimicrobial activity. 25 In this study, E. mitchellii was investigated as a potential source of large quantities ( > 200 mg) of the previously isolated compound, 14-hydroxy-6,12-muuroloadien-15-oic acid (6).…”
mentioning
confidence: 99%